A Review on image compression technique (International Journal of Engineering and Computer Science, 2018)
The demand for images video sequences and computer animation has increased drastically over the years. This has resulted in image and video compression on becoming an important issue in reducing the cost of data storage and transmission.JPEG is currently the accepted standard for still image compression. , but alternative methods are also being explored. Storing images in less memory leads to a direct reduction in storage cost and faster data Hence image compression has proved to be a valuable technique as one solution. In this paper we purpose the lossless method of image compression and decompression using a simple method called Huffman coding.